Collecting in situ meteorological data at European scale to support the copernicus emergency management service - Natschke, M. (2020)
The early warning service of the Copernicus Emergency Management Service (EMS) is composed of the European Flood Awareness System (EFAS) and the European Forest Fire Information System (EFFIS). Both systems provide national and regional authorities as well as the European Commission services with harmonized and added value information to forecasts on floods and forest fire hazards at the European scale. A key component for the operation of of both systems is the Meteorological Data Collection Centre (EMS-MDCC). It has been designed to collect and to validate meteorological observations, to produce a European grid of 5 km by 5 km of essential variables on a 6-hourly basis and to make it available for downstream usage as input to the forecast systems.